The Essence of Teacher Professionalism in Improving the Quality of Education in Elementary Schools - Suratno S; Alifah Fitria Nugraheni; Dhea Putri Kusuma Wardani; Felisiana Fidelia (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Education is a key factor in improving the quality of human resources, where its success is greatly influenced by teacher professionalism as the main implementer of the learning process in elementary schools. However, in practice, various obstacles are still found, such as limitations in the use of technology, lack of innovation in learning, and competency gaps that impact the low quality of learning. This study aims to analyze the concept of teacher professionalism and its role in improving the quality of education in elementary schools. The method used is a literature study by reviewing various scientific sources such as journals, books, and articles relevant to the research topic. Data collection techniques were carried out through documentation studies, while data analysis techniques used a qualitative descriptive approach with stages of data reduction, data presentation, and conclusion drawing. The results of the study show that teacher professionalism is reflected in the mastery of pedagogical, professional, social, and personal competencies that need to be continuously developed. Teachers with high professionalism are able to create effective, creative, and meaningful learning, thereby contributing to improved learning outcomes and the formation of students' character. Therefore, continuous efforts are needed through training, provision of adequate facilities and infrastructure, as well as cooperation between schools, families, and communities in supporting the optimal development of teacher professionalism.